Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2109/jcersj2.119.513
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of hierarchical TiO2 microspheres using a novel titanium complex coordinated by picolinic acid

Abstract: Phase-and morphology-control of TiO 2 was performed by a facile hydrothermal method using a novel water-soluble titanium picolinato complex as a precursor. Single-phase rutile or brookite type titania can be obtained by tailoring the pH of the complex solution. Rutile with a hierarchical microstructure was synthesized using an excess amount of ligand as an additive and the final product consisted of microspheres with mesopores formed by a self-assembly of nanorods. The anisotropic growth of nanorods with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Similarly, brookite particles with typical nanorod shapes were synthesized at pH 10 by hydrothermal treatment at 200 °C for 24 h of the titanium picolinato complex obtained by adding picolinic acid rather than glycolic acid to the peroxo-titanic acid solution [90]. Figure 8.…”
Section: Pure Brookite Powdersmentioning
confidence: 99%
“…Similarly, brookite particles with typical nanorod shapes were synthesized at pH 10 by hydrothermal treatment at 200 °C for 24 h of the titanium picolinato complex obtained by adding picolinic acid rather than glycolic acid to the peroxo-titanic acid solution [90]. Figure 8.…”
Section: Pure Brookite Powdersmentioning
confidence: 99%
“…Hierarchical metastable brookite microspheres have been reported using the hydrothermal treatment of a water-soluble titanium-picolinato complex in an alkaline solution (pH ¼ 10). 27 A surfactantassisted nonaqueous strategy relying on high-temperature aminolysis of titanium carboxylate complexes has been developed to produce anisotropically shaped TiO 2 nanocrystals growing along the [001] direction. 28 However, this synthetic strategy involves extremely complicated procedures or capping complexes that invariably undermine the surface reactivity; thus, water-soluble complexes of titanium are believed to be the most encouraging reagents for the preparation of metastable single phase brookite TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the complex does not undergo hydrolysis in a wide range of pH values (0-14), allowing for the use of various additives. It has been shown that various compounds such as hydroxycarboxylic acid, amino acid and amine can be used as ligands to prepare a stable water-soluble titanium complex [51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%